Pengaruh Pembelajaran dengan Metode Pemberian Tugas dan Resitasi terhadap Hasil Belajar Biologi Siswa Kelas XI SMA Negeri 3 Makassar - Firdaus, Daud (Fakultas MIPA UNM, 2010)
This was a quasy experiment involving control group and experiment one in which the subject was the students of class XI of SMA Negeri 3 Makassar in the school year of 2008/2009. The aim of the research were to knowledge the effect of the learning method in which the students were given assignments and recitation and to compare the study results of the students who were given the assignment and recitation with those who were not. It was done by using Posttest-Only Control Design. The number of the subject was 81 which was chosen by cluster random sampling from 365 students. It was then divided into two groups: experiment group (41 subjects) and control group (40 subjects). The study results of the students in Biology Subject were analyzed by using descriptive statistic and inferensial one. It was shown that the mean of the study results of the students who were given assignment and recitation was higher than of those who were not (t 2,846 > 0,716 with α = 0,05). In conclusion, taking assignment and recitation in the learning process has a positive influence significantly to the study results of the students.